MONITORAMENTO DE EROSÃO LAMINAR EM DIFERENTES USOS DA TERRA, UBERLÂNDIA – MG - José Fernando Pinese Júnior; Lísia Moreira Cruz; Sílvio Carlos Rodrigues (Sociedade & Natureza)
When the soil erosion is accelerated by Humankind action, occur a lot of environmental and economicproblems, just because the soil erosion has influence in environment stability. This research was developedat Glória Experimental Farm/UFU, and its objective was to make analyses and comparisons betweenpluvial soil erosion in seven different land uses. It was collected data about soil moisture, runoff, sedimentstransport and images from each land use in different times for making the photo-comparison to study thedevelopment of the vegetations. In this research were used erosion plots with slope of 5° and a trough inits end part for collecting the water and sediments transported. As a first result, it was observed that anykind of vegetal cover helps in erosion decrease because of the interception of rain drops and the soilradiation by the vegetation leaves. It is possible to affirm that the runoff transports the sediments and the nutrients of soil, and so, the soil cover becomes inappropriate to the agriculture and for another uses.